Thermal conductivity measurement of thin films and bulk materials by 3 omega method - Tham, Wai Hoe. (2011)
This final year project presents the thermal conductivity characterization of Silicon bulk substrate and several thin films such as Silicon dioxide, amorphous Carbon films and Bismuth telluride using the 3-Omega technique. We firstly study the theoretical concept of the 3-Omega method as well as the heat transport mechanism in nano-scaled dimensions. There are two types of circuits which are widely used for the 3-Omega method namely the Wheatstone bridge setup and Differential Amplifier setup. For our project, we will be concentrating on the differential amplifier setup where the circuit is fabricated and validated its feasibility in measuring the thermal conductivities of the samples above. Results obtained are then compared to the Wheatstone bridge setup results as well as the literature reference values. A gold thin wire is deposited on top of the samples which functions as the heater and thermometer which generates the third harmonic voltage. The temperature coefficient resistance of the thin wire is found to be ranged from 0.0021ppm/K to 0.0030ppm/K. The bulk Silicon thermal conductivity was found to be 147±1Wm/K with thermal diffusivity of81.21 10 6m2 / s . The thermal conductivities of 1μm and 100nm thick Silicon dioxide are 1.356 ±0.1Wm/K and 1.0535±0.1Wm/K. As for 100nm thick Carbon thin films, the thermal conductivity is found to be 0.367±0.001Wm/K. Finally, Bismuth telluride film with thickness of 210nm has a thermal conductivity of 0.1575±0.01Wm/K.